Modern migration in Western Africa: studies presented and discussed at the eleventh international African seminar,Dakar,April 1972 - Amin,Samir; International African Institute (Oxford: Oxford University Press, 1974)
This volume presents a selection of research papers on demographic studies of migration from census and other data
Includes index
obn23/01/2019
Loans
Keywords: Migration - internal; Regional planning; Rural development